2022
DOI: 10.1002/ehf2.13904
|View full text |Cite
|
Sign up to set email alerts
|

SYMptoms in chronic heart failure imPACT on burden of treatment (SYMPACT): a cross‐sectional survey

Abstract: AimsThis study aimed to describe patient-reported symptoms and burden of treatment (BoT) experienced by patients with chronic heart failure (CHF). BoT describes the illness workload, individual capacity to perform that work, and resultant impact on the individual. Overwhelming BoT is related to poor quality of life and worse clinical outcomes. This research is the first to explore symptoms and BoT in people with CHF, in the UK. Methods and resultsThis is a cross-sectional questionnaire survey of CHF patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…These findings provide evidence that symptoms interact with a person's ability to participate in the self-care work, providing explanations into why PETS workload index scores were lower than expected (Austin et al, 2022), through the identification of intervening factors. All participants described situations where symptoms of CHF had made the work of illness management more difficult, where the more intense symptoms became, the more difficult selfcare work became.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These findings provide evidence that symptoms interact with a person's ability to participate in the self-care work, providing explanations into why PETS workload index scores were lower than expected (Austin et al, 2022), through the identification of intervening factors. All participants described situations where symptoms of CHF had made the work of illness management more difficult, where the more intense symptoms became, the more difficult selfcare work became.…”
Section: Discussionmentioning
confidence: 72%
“…In our previous work (Austin et al, 2022), validated tools measuring treatment burden were used in a sample of people with CHF where interactions with symptoms were explored. Symptoms were measured with heart failure symptom survey (HFSS) (Pozehl et al, 2006) and Minnesota living with heart failure questionnaire (MLHFS) (Bilbao et al, 2016; Rector, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is often induced by improper diet, overwork, and repeated attacks of exogenous pathogens, among others. These factors result in conditions that can be explained by the TCM symptoms heart-Qi deficiency and heart-Yang deficiency[ 21 , 22 ]. Our study revealed that the curative effects of Luhong formula on TCM syndromes and cardiac function were significantly better in the research group than in the control group, indicating the significant advantages of Luhong formula in relieving CHF symptoms and improving cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, results may be less generalizable to patients receiving transplants at other centers, including centers outside the United States. Interestingly, treatment burden as measured by the PETS has been found to be relevant to patients with chronic health conditions in other countries with different healthcare systems, including the United Kingdom and Norway [ 37 39 ]. Third, our cohort had relatively low representation of racial/ethnic minorities and the less formally educated, and future studies should include a more diverse cohort.…”
Section: Discussionmentioning
confidence: 99%